2020
DOI: 10.1155/2020/6665996
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Mechanics Characteristics of CFRP Strengthening of Highway Tunnels at Different Damage States

Abstract: Cracks and other diseases may occur in the long-term operation of highway tunnels and reduce the structural load-carrying capacity. Strengthening using carbon fiber reinforced polymer (CFRP) sheets and other materials could extend the service time of the tunnels. However, the process of strengthening tunnels is remarkably different from the process of strengthening aboveground structures because of the secondary load. In order to understand the development of stress and deformation of strengthened tunnels unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It was found that dipyridamole significantly reduced the thrombus formation of the polyurethane surface and significantly reduced the adhesion of platelets, thereby improving the blood compatibility of the polyurethane [5]. Ozkan et al pointed out that it is necessary to enhance the positive attitude of patients to treatment, reduce their anxiety, depression and other negative emotions, extend the survival period of cancer patients, improve their quality of life, and improve the recovery rate of patients; we believe that we will provide clinical standards for this illness [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that dipyridamole significantly reduced the thrombus formation of the polyurethane surface and significantly reduced the adhesion of platelets, thereby improving the blood compatibility of the polyurethane [5]. Ozkan et al pointed out that it is necessary to enhance the positive attitude of patients to treatment, reduce their anxiety, depression and other negative emotions, extend the survival period of cancer patients, improve their quality of life, and improve the recovery rate of patients; we believe that we will provide clinical standards for this illness [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Only the input vector that meets this condition can contribute to the SVM model. is is the sparsity of the SVM solution [9,10].…”
Section: Treatmentmentioning
confidence: 99%
“…Therefore, research on the damage of water conveyance tunnels and the related treatment measures have attracted much attention from scholars. Carbon fiber reinforced plastics (CFRPs) have the advantages of a high strength-weight ratio, short installation period, minimal impact on the concrete structure and adaptability to curved surfaces (Sun et al, 2017;Yang et al, 2019;Liu et al, 2020). Since CFRP reinforcement technology can effectively limit the continuous expansion of concrete cracks and prevent the lining from being broken and spalling, it has gradually become a common and effective way to strengthen the internal surface of a pressure tunnel lining (Wang and Lee, 2012;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%